Neonatal Quality Assurance, Morbidity and Mortality: Surveillance and Analysis with Microcomputer Techniques - Bash, Margaret C. (1987)
This paper describes a system used to monitor the quality of care provided in our Intensive Care Nursery. A special form was developed to collect data, and a microcomputer is used to store and analyze the data.